The level of anxiety in patients with chronic obstructive pulmonary disease: diagnosis, differential diagnosis and treatment approaches - Pertseva, T. O.; Konopkina, L. I.; Veresa, O. V.; Huba, Yu. V. (Zaporozhye Medical Journal, 2016)
Mental disorders including increased anxiety are comorbid conditions in chronic obstructive pulmonary disease (COPD). They have a negative influence on the general condition of patients, their quality of life, and commitment to long-term treatment, impair the effectiveness of rehabilitation. Recently, researchers devoted much attention to the study of causal relationships between increased anxiety, clinical and functional manifestations of COPD. Objective: to establish a link between clinical manifestations and the level of anxiety in patients with COPD. Methods and results. We examined 77 patients with COPD. A survey of patients included general clinical methods, evaluation of clinical symptoms, including by means of questionnaires, spirometry. Determining the level of anxiety was made using Hospital Anxiety and Depression Scale. The final evaluation of the mental state of patients was conducted by psychiatrist. COPD patients with increased anxiety and with normal levels of anxiety did not have differences in demographic parameters and the level of ventilation disorders. However, in COPD patients with increased anxiety the severity of dyspnea and the severity of symptoms is generally more severe than in patients with normal levels of anxiety. Conclusion. In identifying increased anxiety in patients should be advised to consult by psychiatrist. At the same time, the normal level of anxiety in patients with COPD by questionnaire HADS-anxiety does not exclude the possible presence of other changes in mental status.